Evaluation of efficacy of restorative dental treatment provided under general anesthesia at hospitalized pediatric dental patients of Isfahan - Alireza Eshghi; Mahdi Jafarzadeh Samani; Naghme Feyzi Najafi; Maryam Hajiahmadi (Wolters Kluwer Medknow Publications, 2012)
Background: General anesthesia (GA) allows dental treatment to be rendered under optimal conditions, theoretically ensuring ideal outcomes. The aim of this study was to determine the efficacy of restorative dental procedures performed under GA. Materials and Methods: In this cross-sectional retrospective study, 305 pediatric patients who had been treated under GA 6 to 24 months before our survey at Isfahan's hospitalized dentistry center were examined. The examination was performed on dental chair with oral mirror and dental probe. The results were recorded in a special form for each patient for statistical analysis and evaluation of restorations to be successful or failed. Statistical analysis was performed by chi-square and fisher exact tests for comparison between success rates of restorations and Kendall's tau-b test for evaluating the effect of time on success rates of them (P < 0.05). Results: Stainless steel crown restorations had significantly better results vs class I and class II amalgam and class I and class II tooth color restorations. All types of posterior tooth color restorations had statistically same results with amalgam restorations. Anterior composite resin build-up represented significantly low success rates. The failure rates of stainless steel crown and anterior composite resin build-up restorations did not correlate with the time of follow-up (P = 0.344 and P = 0.091, respectively). Conclusion: Stainless steel crown restorations had significantly better results vs other posterior restorations. The failure rates of stainless steel crown and anterior composite resin build-up restorations did not correlate with the time of follow-up in comparison of other restorations.